A review of the genus Alcathousiella Monné, 2005 (Coleoptera, Cerambycidae) - Nascimento, Francisco E. de L.; Monné, Miguel A.; Wappes, James E. (European Journal of Taxonomy, 2021)
The Acanthocinini genus Alcathousiella Monné, 2005 (Coleoptera, Cerambycidae, Lamiinae) is revised with both the genus and the type species, Alcathousiella polyrhaphoides (White, 1855) redescribed. New country records for the species, greatly expanding its known distribution in South America, are also presented. Lastly, Alcathousiella giesberti sp. nov., from Nicaragua, Costa Rica and Panama is described and illustrated.